The Road to Resilience: Traveling the Path Less Followed to Realize What is Possible - Jennifer Fortuna (Scholarworks @ WMU, 2019)
Dr. Bernadette Mineo, PhD, OTR/L, an occupational therapist and mixed media artist based in Portland, Oregon, provided the cover art for the Winter 2019 issue of The Open Journal of Occupational Therapy (OJOT). The piece, titled "Paper Dolls" (2009), consists of 37 individual paper doll sculptures made from mixed media. Dr. Mineo believes that being an artist is about connecting with one's creative heart. Her art is about being playful, challenging oneself, and setting up experiments. Engaging in a daily creative art practice has brought joy to Dr. Mineo's life. Art has empowered her to take risks, build resilience, and discover what is possible. By sharing her daily art practice with others, Dr. Mineo aims to promote creative solutions and hope in the face of challenging situations.